Lawrence Gostin's Enthusiastic Globalism - Latham, Stephen R. (The Hastings Center report, 2016)
These are hard days for globalism. A major candidate for the United States presidency ran on an anti-immigration, anti-free-trade platform and denounced such venerable international institutions as the North Atlantic Treaty Organization (“obsolete”) and the United Nations (“a political game”). The European Union is under threat after the vote for Brexit; the Euro is under strain. China is denouncing and ignoring the result of an international arbitration over its claims to the South China Sea. Nationalist, xenophobic political parties are in the ascendency around the world, buoyed by the fears and pains of populations for whom global trade has been no boon and to whom waves of new immigrants seem threatening both economically and socially. So it is both strange and uplifting, in this atmosphere, to encounter the ambitious and enthusiastic globalism of Lawrence Gostin's important, field-founding work, Global Health Law. Equal parts encyclopedia and manifesto, the book seeks both to provide exhaustive and up-to-date descriptions of the already-substantial body of international health law and of its implementing institutions and to chart Gostin's vision for their vigorous expansion. And that vision is nothing if not expansive.